2006
DOI: 10.1186/1471-2458-6-36
|View full text |Cite
|
Sign up to set email alerts
|

The importance of comorbidity in analysing patient costs in Swedish primary care

Abstract: BackgroundThe objective was to explore the usefulness of the morbidity risk adjustment system Adjusted Clinical Groups® (ACG), in comparison with age and gender, in explaining and estimating patient costs on an individual level in Swedish primary health care. Data were retrieved from two primary health care centres in southeastern Sweden.MethodsA cross-sectional observational study. Data from electronic patient registers from the two centres were retrieved for 2001 and 2002, and patients were grouped into ACGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
4
25
0
1
Order By: Relevance
“…Therefore, depression and back pain were handled to a great extent by GPs, and for these combinations, significant reductions in all types of costs were seen. Hence, in the management of multimorbidities, there might be opportunities for coordinating these healthcare processes within primary care in order to reduce costs 25. The coordination of care among persons with multiple health conditions is also important for the quality of care and to avoid unnecessary hospitalisations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, depression and back pain were handled to a great extent by GPs, and for these combinations, significant reductions in all types of costs were seen. Hence, in the management of multimorbidities, there might be opportunities for coordinating these healthcare processes within primary care in order to reduce costs 25. The coordination of care among persons with multiple health conditions is also important for the quality of care and to avoid unnecessary hospitalisations.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, a Swedish study found that the variation in individual patient costs was substantially different within different age groups, as well as within different co-morbidity groups. 13 37.7% of individual patient costs in the Swedish study could be explained by co-morbidities, while age and gender accounted for an additional 0.8%.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, they are proprietary systems, which are not transparent and difficult to use. The ACG system has been demonstrated to be sensitive to the accuracy of classification and coding of diagnoses by GPs, thus introducing potential bias into the estimates of practices' morbidity scores [8]. Other case-mix systems, such as that based on 17 Quality of Framework concepts [44], have demonstrated better performance than ACG (R 2 ¼ 0.31 vs. R 2 ¼ 0.27) in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ACG seems to be the most valid method for predicting patient or health service costs, it is a proprietary risk adjustment system that tends to be not transparent, very expensive, and difficult to understand for the final user [8,16,17]. In addition, the 68 mutually exclusive ACG categories are not specifically targeted at patients with chronic disease, and are unable to sufficiently capture the prospective burden of chronic coexistent diseases [16,17].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation